Impact of feed carbohydrates and nitrogen source on the production of soluble microbial products (SMPs) in anaerobic digestion. (1st October 2017) - Le, Chencheng; Stuckey, David C.
Abstract: Six stirred fill-and-draw batch reactors with a range of carbohydrate feeds (glucose, fructose and sucrose), and nitrogen sources (NH4 Cl, urea) at various concentrations were used to investigate the effect of feed composition on the production of soluble microbial products (SMPs) during anaerobic digestion (AD). To gain greater insights into the SMPs produced, the composition of various fractions was analyzed, while the low molecular weight (MW) SMPs generated with different feeds and nutrients were collected and chemically analyzed using GC-MS. Other organic solutes such as free amino acids were determined using HPLC, and this level of chemical analysis has never been carried out in past work because of analytical limitations. It was found that the presence of ammonium salts rather than urea at 200 mg/L stimulated the production of not only volatile fatty acids, but also SMPs of different MW fractions, and reduced the production of biogas significantly. The study also revealed that the type of SMP that dominates in a particular system depends on the chemical characteristics of the feed, and this insight has implications on the composition of the effluent from anaerobic digesters (and their potential chlorination by-products), and membrane fouling in membrane bioreactors. Graphical abstract: Highlights: First study on the effect of nitrogen-feed on the formation of SMPs. Reveal the impact of different substrates/nutrients on wastewater quality. Composition of substrate influences the metabolic pathways and AD performance. Understanding nutritional conditions ensure a cooperative bacterial symbiosis.